Avaliação do teste Quantiferon TB Gold in tube no diagnóstico de infecção latente pelo Mycobacterium tuberculosis em profissionais de saúde da atenção básica - Souza, Fernanda Mattos de (2014)
Background: A new interferon-γ release assay, QuantiFERON-TB (QFT) test, poses as an alternative test for the diagnosis of latent Mycobacterium tuberculosis infection (LTBI). Here, we compared the performance of QFT with tuberculin skin test (TST) measured at two different cut-off points among primary health care workers (HCW) in Brazil. Methods: A cross-sectional study was carried out among HCWs in four Brazilian cities with a known history of high incidence of TB. Results of the QFT were compared to TST results based on both ≥5mm and ≥10 mm as cut-off points. Results: We enrolled 632 HCWs. When the cut-off value of ≥10 mm was used, agreement between QFT and TST was 69% (k=0.31), and when the cut-off of ≥5 mm was chosen, the agreement was 57% (k=0.22). We investigated possible factors of discordance of TST vs QFT. Compared to the TST-/QFT– group, the risk factors identified for discordance at the TST+/QFT- group when the TST cut-off of ≥5 mm was used were age between 41-45 [OR=2.70; CI 95%: 1.32-5.51] and 46-64 [OR=2.04; CI 95%: 1.05-3.93], BCG scar [OR=2.72; CI 95%: 1.40-5.25], and having worked only in primary health care [OR=2.30; CI 95%: 1.09-4.86]. On the other hand, for the cut-off of ≥10 mm BCG scar [OR=2.26; CI 95%: 1.03-4.91], being a household contact of a TB patient [OR=1.72; CI 95%: 1.01-2.92] and having had a previous TST [OR=1.66; CI 95%: 1.05-2.62], were significant. Interestingly, discordance observed at the TST-/QFT+ group showed no statistically significant association with any of the variables regardless of TST cut-off value used. Conclusions: Although we identified BCG vaccination to contribute to the discordance in spite of TST cut-offs, the current Brazilians recommendation for the initiation of LTBI treatment, based on TST, should not be changed, based on QFT limitations and decreased accuracy of the method.